2018
DOI: 10.1002/stem.2802
|View full text |Cite
|
Sign up to set email alerts
|

Prior Treatment with Anti-High Mobility Group Box-1 Antibody Boosts Human Neural Stem Cell Transplantation-Mediated Functional Recovery After Spinal Cord Injury

Abstract: Together with residual host neurons, transplanted neural stem cell (NSC)-derived neurons play a critical role in reconstructing disrupted neural circuits after spinal cord injury (SCI). Since a large number of tracts are disrupted and the majority of host neurons die around the lesion site as the damage spreads, minimizing this spreading and preserving the lesion site are important for attaining further improvements in reconstruction. High mobility group box-1 (HMGB1) is a damage-associated molecular pattern p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 55 publications
2
47
0
Order By: Relevance
“…This is also consistent with a previous report in which SC-type fetal NPC engraftment was shown to improve the motor function of SCI mice with mild lesions but not severe lesions [ 14 ]. The importance of lesion severity is also highlighted by the recent finding that treatment with anti-HMGB1 antibody reduced the lesion size of the injured spinal cord and improved motor function recovery synergistically with NPC transplantation [ 34 ]. To exploit the full potential of NPCs for SCI treatment, the use of such an additional approach to minimize the lesion size will be important.…”
Section: Discussionmentioning
confidence: 99%
“…This is also consistent with a previous report in which SC-type fetal NPC engraftment was shown to improve the motor function of SCI mice with mild lesions but not severe lesions [ 14 ]. The importance of lesion severity is also highlighted by the recent finding that treatment with anti-HMGB1 antibody reduced the lesion size of the injured spinal cord and improved motor function recovery synergistically with NPC transplantation [ 34 ]. To exploit the full potential of NPCs for SCI treatment, the use of such an additional approach to minimize the lesion size will be important.…”
Section: Discussionmentioning
confidence: 99%
“…High mobility group box-1 (HMGB1) is released from neurons during ischemic injury, traumatic injury, intracerebral hemorrhage, and spinal cord injury [1][2][3][4][5][6]. The translocation of HMGB1 in neurons and their subsequent release were demonstrated in primary culture after the insult of glucose deprivation and glutamate treatment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the different treatments, 60 Wistar rats were divided into four experimental groups, in order to minimize the sacrifice and suffering of animals, we refer to previous experiments and cancel the sham operation group. 28 The control group is Group Adult female Wistar rats (230-250 g) were used for spinal cord transection. Animals were acclimatized for at least one weeks before surgery.…”
Section: Spinal Cord Transection and Transplantationmentioning
confidence: 99%
“…25 While several studies have shown that single SC repair of SCI is still limited, researchers try to transplant it with other stem cells in order to achieve better effects. [26][27][28] Coculture of SCs with neural stem cells (NSCs) can remarkably increase the proportion of neuron differentiation and effectively improve the recovery of nerve endings. 29 Polycaprolactone (PCL) is an aliphatic, biodegradable, nontoxic polyester with good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%